Macrobenthic Composition of Sea Water Associated with Seagrass in East and West Portions of the Igang Bay, Nueva Valencia, Guimaras - De La Cruz, Mary Jean L.; Flores, June Raymund Peter; Magramo, Melchor M.; Madas, Christy; Terunez, Marlon (JPAIR Multidisciplinary Research, 2012)
The macrobenthic invertebrates are associated with seagrass communities in East and West at the Igang Bay, Nueva Valencia, Guimaras. Seven groups were found in West Igang which includes the hard coral, gastropod, bivalve, soft coral, starfish, limpet, hermit crab and cowrie while eight groups composed of bivalve, gastropod, snail, cowrie, hard coral, hermit crab and sponge were found in the seagrass community of East Igang. Results show that gastropod was the dominating group in both sites. The hard coral group was the most frequent to occur in West Igang while the gastropod in East Igang was frequently observed. Common groups in both sites were hard coral, gastropod, bivalve, and cowrie. West Igang had higher diversity of macrobenthos (H’ = 0.608) than the East Igang with (H’ = 0.513). Both sites have sandy, silty-muddy type of substrates although some portions of West Igang were rocky. Salinity ranged from 28 to 30 parts per thousand and temperature from 20.67 to 32.67 degrees Celsius. Water depth recorded ranged from 0.43 to 0.60 meters. The higher variability of substrates in West Igang probably promoted the higher diversity of macrobenthic groups in the area suitable for different attachments and mobility along with denser growth of seagrass in the said site.